Oral hygiene and the overall survival of head and neck cancer patients - Chan‐Chi Chang; Wei‐Ting Lee; Jenn‐Ren Hsiao; Chun‐Yen Ou; Cheng‐Chih Huang; Sen‐Tien Tsai; Ken‐Chung Chen; Jehn‐Shyun Huang; Tung‐Yiu Wong; Yu‐Hsuan Lai; Yuan‐Hua Wu; Wei‐Ting Hsueh; et al. (Cancer Medicine, 2019)
Abstract Poor oral hygiene is an established risk factor of head and neck cancer (HNC); however, its role in the survival of HNC patients is unclear. This study evaluated the association between oral hygiene habits, including regular dental visits, frequency of tooth brushing, and use of dental floss, and the overall survival (OS) of HNC patients using interview data collected from 740 HNC patients. In addition, the interactions between oral hygiene and the polymorphisms of TLR2 and TLR4 on the OS of HNC patients were assessed. The analysis indicated that poor oral hygiene was significantly associated with poorer OS of HNC patients (hazard ratio (HR) = 1.38, 95% confidence interval (CI): 1.03‐1.86). This association was modified by a single nucleotide polymorphism, rs11536889, of TLR4. A significant association between poor oral hygiene and worse survival of HNC was observed among those with the CG or CC genotype (HR = 2.32, 95% CI: 1.41‐3.82) but not among those with the GG genotype (HR = 0.95, 95% CI: 0.65‐1.40). Our results suggested that poor oral hygiene is not only a risk factor but may also be a prognostic factor of HNC.